Novel cryoballoon to isolate pulmonary veins in patients with paroxysmal atrial fibrillation: one-year outcomes in a multicenter study. (14th October 2021) - Martin, A; Breskovic, T; Ouss, A; Dekker, L; Yap, S C; Bhagwandien, R; Cielen, N; Albrecht, E M; Richards, E; Tran, B; Lever, N; Anic, A
Abstract: Background: Recently, a novel cryoballoon (CB; POLARx) has been developed with increased steerability which maintains size and pressure throughout the ablation. Initial clinical data has demonstrated acute procedural safety and efficacy in de novo pulmonary vein isolation (PVI) procedures in patients with paroxysmal atrial fibrillation (AF). However, there are limited studies demonstrating the long-term efficacy of the CB. Purpose: To evaluate the long-term safety and efficacy of the novel CB in treating paroxysmal AF. Methods: This was a non-randomized, prospective, multi-center study. Fifty-eight consecutive patients with paroxysmal AF were enrolled at 4 centers for de novo PVI procedures. Cryoablation was delivered for 180s if time to isolation was ≤60s. Otherwise a 240s cryoablation was performed. PVI was confirmed with entrance and exit block testing. Patients were followed for 1 year with 24-hour Holter monitoring at 3, 6, and 12 months. After a 3-month blanking period, recurrence was defined as having any documented, symptomatic episode(s) of AF or atrial tachycardia. Results: Acute isolation with the CB was achieved in 230 of 231 pulmonary veins (99.6%) with 5.2±1.5 cryoapplications per patient (1.3±0.6 cryoapplications per vein). There were 4 patients (6.9%) with phrenic nerve injury (3 resolved during the index procedure; 1 resolved at 6 months follow-up). One serious adverse device event was reported: femoral arterial embolism event occurring 2 weeks post index procedure (1.7%). Of the 56 patients that had complete 12-month follow-up, 43 (76.8%) were free from recurrent atrial arrhythmias. Conclusion: Initial multicenter clinical experience with the novel CB has demonstrated long-term safety and efficacy of PVI in patients with paroxysmal AF. Further studies are underway to confirm these findings. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boston Scientific